Análise do processo de licenciamento ambiental brasileiro : o caso da mineração na serra do Gandarela - Scatolini, Tiago Luis Castro (Universidade Federal de São Carlos, 2015)
In recent years we have witnessed a permanent offensive sectors of the federal government and a very strong lobby of construction companies, mining companies and other companies interested in easing the environmental licensing standards. To this campaign added the deconstruction efforts of environmental legislation, undertaken by a joint forces located inside and outside of our legislatures. We emphasize in particular the limited participation of government institutions in the licensing process and advocate to be revised the current contracting model. Thus, this study will seek, in the light of network analysis theory and mutual comparison between the results and analysis of a brazilian environmental impact study and an academic research project for the same lithology, analyze the limits and contradictions of study brazilian environmental impact. The readback proposed aims to illustrate the possible existence of control by private interests in the studies of environmental impact as a result of their employment structure and governmental control. The analysis of the concession of natural areas operating license process is necessary given the importance of this study within the sustainable development theme, as well as their hiring process.
Keywords: Política ambiental; Licenciamento ambiental; Desenvolvimento sustentável; Bioespeleologia; Serra do Gandarela; Environmental policy; Environmental licensing; Sustainable development; Biospeleology; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::CIENCIA POLITICA